Judicial Exposition of Gender Justice as a Constitutional Mandate: A Narrative from India - Shipra Gupta (Brawijaya Law Journal, 2020)
The catalytic role played by the Indian judiciary in providing visibility to the ‘covert social prejudices’ against females has succeeded in alleviating the condition of women in our patriarchal society. This paper strives to highlight the proactive role played by the judiciary in recent years, addressing women concerns in a different light, which were hitherto unconditionally accepted with complacence. Purposive approach adopted by the judiciary in interpreting existing laws, manifests adherence to the constitutional mandate of gender equality. Further, an attempt has been made to identify the areas where judicial action has fallen short in bringing about real justice to women. The research is primarily based on the normative method presenting qualitative analysis of the constitutional and legislative provisions and their judicial exposition. The paper concludes that judicial creativity needs the backing of social acceptability to bring about real social transformation towards the constitutional mandate of gender justice.